Difusão de material informativo sobre o descarte de resíduos radiológicos entre acadêmicos de odontologia e cirurgiões-dentistas da região Sul do Brasil - Bohner, Lauren Oliveira Lima (2011)
The radiologic material used in dental offices products environmental hazard if not disposedproperly, because the silver, present in chemical solutions used during the development process, isconsidered toxic to humans. The management of Health Services is the process to minimizing theadverse effects caused by toxic waste, reducing the environmental impact. The healthprofessionals knowledge about the disposal process is very important, in order to developingawareness in the academic environment. This study aims to disseminating information on theWaste Management of Health Services among dental students and dentists. In this sense, it wasdeveloped posters and leaflets about the environmental impact caused by the incorrect radiological waste disposal and waste management of Health Services, and distributed in theFederal University of Santa Catarina (UFSC) Dentistry University and Dental Offices and in the citiesof Florianópolis, SC. The leaflets were distributed in one hundred offices, and six posters weredistributed in community colleges. Orientation programs are necessary to promote professionaleducation and awareness about the appropriate approach to waste disposal, as well as theenvironmental impact caused by its breach.